FACTORS THAT INFLUENCE GREEN ACCOUNTING AND ITS EFFECT ON FIRM VALUE IN COMPANIES GREEN AWARD WINNERS INDUSTRY AWARD-WINNING COMPANIES LISTED ON THE INDONESIANSTOCK EXCHANGE PERIOD 2019 - 2023 - Nadeak, Heri Imanuel; Simanjuntak, Arthur; Sagala, Farida; Ginting, Mitha Christina (Program Studi Akuntansi Universitas Simalungun, 2025)
This study aims to test and analyze the factors that influence Green Accounting and its effect on firm value in Green Industry Award-winning companies listed on the Indonesia Stock Exchange for the 2019 - 2023 period. The population in this study were all companies that received gold and green proper awards, namely 23 companies and a sample of 11 companies. The analysis method used is multiple linear regression analysis method using spss 26. The results showed that partially profitability had a positive and significant effect on Green Accounting, Leverage and Liquidity partially had a negative and insignificant effect, Profitabiits and Liquidity partially had a positive and significant effect on firm value, Leverage partially had a positive and insignificant effect on firm value, Green Accounting partially had a negative and insignificant effect on firm value. While simultaneously Profitability, Leverage and Liquidity have a significant and significant effect on Green Accounting and Profitability, Leverage, Liquidity and Green Accounting simultaneously have a significant and significant effect on firm value. The results of testing the coefficient of determination for profitability, Leverage and Green Accounting variables are able to explain the Green Accounting variable by 13.8% and the remaining 86.2% is influenced by variables